2019
DOI: 10.1177/0300060519887276
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose apatinib monotherapy in advanced chemotherapy-refractory small cell lung cancer: a case series and literature review

Abstract: The therapeutic regimen for small cell lung cancer (SCLC) has changed little in the past several decades. Apatinib is a small molecule inhibitor of vascular endothelial growth factor receptor-2 tyrosine kinase. Apatinib has demonstrated efficacy against advanced gastric cancer and breast cancer, and recent studies have also reported its successful use in non-SCLC; however, its efficacy in SCLC remains unclear. In this study, we used apatinib as salvage therapy for chemotherapy-refractory SCLC. Five male patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
1
4
0
Order By: Relevance
“… 20 Meanwhile, Liu’s report in the same period suggested that apatinib had partial reactions but only mild side effects, including mild hypertension, vomiting and hand-foot syndrome, which could be controlled. 21 According to our study, there was no significant difference in the incidence of adverse drug reactions between the two groups (p=0.23), which also confirmed that the combination of apatinib and chemotherapy did not increase adverse reactions.…”
Section: Discussionsupporting
confidence: 75%
“… 20 Meanwhile, Liu’s report in the same period suggested that apatinib had partial reactions but only mild side effects, including mild hypertension, vomiting and hand-foot syndrome, which could be controlled. 21 According to our study, there was no significant difference in the incidence of adverse drug reactions between the two groups (p=0.23), which also confirmed that the combination of apatinib and chemotherapy did not increase adverse reactions.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have confirmed a close correlation between the VEGF and lymph node metastasis in NSCLC, and lymph node metastasis is the primary route of lung cancer metastasis. As such, it is speculated that VEGF receptor inhibitors play an important role in improving the prognosis of patients with oligometastatic lung cancer [ 10 ]. However, there is a paucity of studies reporting the application effect of apatinib in patients with oligometastatic lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The standard dose of apatinib in patients with gastric cancer is 850 mg, while the common application dose is 500 mg according to the use in of NSCLC and SCLC. [ 32 , 33 ] This suggests that the tolerance of different tumor species to apatinib is different, hence, the application dose should be individualized and an initial dose of 250 mg can also be selected clinically. In this report, low-dose apatinib monotherapy eventually eliminated residual tumors in a patient with primary MNSGCT.…”
Section: Discussionmentioning
confidence: 99%
“…The initial dose of apatinib was 500 mg per day, but it was reduced to 250 mg due to side effects of hoarseness, hypertension, HFSR, and proteinuria. The standard dose of apatinib in patients with gastric cancer is 850 mg, while the common application dose is 500 mg according to the use in of NSCLC and SCLC [32,33] . This suggests that the tolerance of different tumor species to apatinib is different, hence, the application dose should be individualized and an initial dose of 250 mg can also be selected clinically.…”
Section: Discussionmentioning
confidence: 99%